2017
DOI: 10.1097/bcr.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Enema

Abstract: Hydrocarbons are a wide-ranging group of flammable chemicals and are often used in suicide attempts either by ingestion or as an accelerant in self-immolation. In this case study, we present a 37-year-old female who suffered 6% TBSA partial-thickness burns to her perineum and buttocks, which she claims resulted from diarrhea after ingesting a bottle of lighter fluid. The patient underwent decontamination and medical treatment for her burns and during her inpatient stay, it became apparent that the burns were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This patient was previously treated with a STSG, which failed and was subsequently managed conservatively with dressings. 5 Fino et al reported a case of self-inflicted 0.5% TBSA full-thickness chemical burn from acoustic substance. This was managed conservatively, and healing was achieved six weeks after injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient was previously treated with a STSG, which failed and was subsequently managed conservatively with dressings. 5 Fino et al reported a case of self-inflicted 0.5% TBSA full-thickness chemical burn from acoustic substance. This was managed conservatively, and healing was achieved six weeks after injury.…”
Section: Discussionmentioning
confidence: 99%
“…3 Another case with hydrocarbon enema to the perineum and buttocks was described by Mygatt et al and had 6% TBSA partial-thickness burns treated conservatively. 4 Idicula et al described a case of factious disorder with a history of frequent self-inflicted burns while at work from an unknown chemical agent. This patient was previously treated with a STSG, which failed and was subsequently managed conservatively with dressings.…”
Section: Discussionmentioning
confidence: 99%